Prevalence and distribution of hepatitis C virus genotypes in Spain during the 2000‐2015 period (the GEHEP 005 study). Issue 9 (10th April 2017) - Aguilera, A.; Navarro, D.; Rodríguez‐Frias, F.; Viciana, I.; Martínez‐Sapiña, A. M.; Rodríguez, M. J.; Martró, E.; Lozano, M. C.; Coletta, E.; Cardeñoso, L.; Suárez, A.; Trigo, M.; et al.
Summary: We report the largest study on the prevalence and distribution of HCV genotypes in Spain (2000‐2015), and we relate them with clinical, epidemiological and virological factors. Patients from 29 hospitals in 10 autonomous communities (Andalusia, Aragon, Castilla‐Leon, Catalonia, Galicia, Canary Islands, Madrid Community, Valencian Community, Murcia Region and Basque Country) have been studied. Annual distribution of HCV genotypes and subtypes, as well as gender, age, transmission route, HIV and/or HBV coinfection, and treatment details were recorded. We included 48595 chronically HCV‐infected patients with the following characteristics: median age 51 years (IQR, 44‐58), 67.9% male, 19.1% HIV‐coinfected, 23.5% HBV‐coinfected. Parenteral transmission route was the most frequent (58.7%). Genotype distribution was 66.9% GT1 (24.9% subtype 1a and 37.9% subtype 1b), 2.8% GT2, 17.3% GT3, 11.4% GT4 and 0.1% GT5 and 0.02% GT6. LiPA was the most widely HCV genotyping test used (52.4%). HCV subtype 1a and genotypes 3 and 4 were closely associated with male gender, parenteral route of infection and HIV and HBV coinfection; in contrast, subtype 1b and genotype 2 were associated with female gender, nonparenteral route and mono‐infection. Age was related to genotype distribution, and different patterns of distribution and biodiversity index were observed between different geographical areas. Finally, we describe how treatment and changes in transmission routes may have affected HCV genotype prevalence and distribution patterns. We present the most recent data on molecular epidemiology of hepatitis C virus in Spain. This study confirms that genotype distributions vary with age, sex, HIV and HBV coinfection and within geographical areas and epidemiological groups.